Adolescents perception of the COVID-19 pandemic restrictions and associated mental health and well-being: gender, age and socioeconomic differences in 22 countries - Franziska Reiss; Alina Cosma; Michela Bersia; Michael Erhart; Paola Dalmasso; Janine Devine; Sabina Hulbert; Carolina Catunda; Inese Gobina; Ariela Giladi; Helena Jeriček Klanšček; Ulrike Ravens-Sieberer (BMC, 2024)
Abstract Background The COVID-19-pandemic has had a profound impact on the lives of adolescents worldwide. This study examined the subjective perception of the COVID-19 pandemic measures and its association with mental health and well-being (i.e., loneliness, life satisfaction and multiple health complaints) among 13- and 15-years-old adolescents from 22 countries. Methods Data from the cross-national Health Behaviour in School-aged Children (HBSC) 2021/22 study were used from representative samples of 22 countries (N = 67,544; 51.9% girls). The self-perceived impact of COVID-19 measure comprised 10 items asking about the impact on several dimensions of adolescent lives (e.g., relationships with family and friends, health, or eating behaviours). Measures of loneliness, multiple health complaints, and life satisfaction were included as indicators of mental health and well-being. A non-parametric multilevel latent class analysis considering individual and country-levels was conducted to identify classes of self-perceived impact of the COVID-19 measures. Multilevel logistic regression models adjusted by age and socioeconomic status were applied to assess the association between COVID-19 measure impact classes and mental health. Results Three classes were identified on individual level encompassing a neutral (51%), positive (31%), or negative (18%) perception of COVID-19 measures. A third of the adolescents reported a positive impact of the pandemic measures. The distribution of classes was heterogeneous within and across countries. Within the positive COVID-19 measure impact class, social relationships were the most important dimension, whereas mental health problems were mostly represented within the negative COVID-19 measure impact class. Girls with a negative perception of pandemic measures showed higher levels of loneliness and multiple health complaints and lower life satisfaction. 15-year-old adolescents and those with a low socioeconomic status reported higher levels of loneliness and lower life satisfaction. Conclusions The majority of adolescents perceived the pandemic measures as neutral or positive. Girls, 15-year-old adolescents, and those with low socioeconomic status were at higher risk of suffering from pandemic measures and associated problems of loneliness, multiple health complaints, and low life satisfaction. We conclude that adolescent's mental health and well-being should be considered in the decision-making process by ensuring that the unique challenges of adolescents are adequately addressed in policies.